Death Due to Diarrhea: Before and After National Rehydration Program - W.A.F.J. Tumbelaka; Sunoto Sunoto (Indonesian Pediatric Society, 1978)
Diarrheal diseases still constitute one of the major causes of morbidity and mortality in Indonesian children. The ertiology is multi-complex as in other developing countries. In 1974 a National Seminar on Rehydration was held in Jakarta and a rehydration program started with a standardized treatment of Ringer's Lactate and oral rehydration (ROSE SYSTEM). As a result the case fatality rate of diarrheal diseases has been dramatically reduced for for gastroenteritis and cholera.